Neonatal liver failure: A refractory case to medical treatment. (24th May 2012) - Shetty, M; Schulze, S; Ong, E
Abstract : Neonatal liver failure (NLF) is rare and carries a high mortality. Common aetiologies include neonatal haemochromatosis (NH), haematological malignancies, viral infections and liver-based metabolic defects. Early diagnosis and referral to a paediatric liver centre is recommended as liver transplantation is the only definitive treatment when supportive or a disease-specific treatment fails. A baby girl was born by Emergency LSCS for pathological cardiotocography at 33+2 weeks of gestation. Her mother had been previously well and had normal pregnancy. She was birth in poor condition requiring cardiopulmonary resuscitation. She was transferred to a level 2 neonatal unit for ventilator management. At birth she had coagulopathy which remained refractory to medical treatment. She required multiple ionotropes, multiple blood products and high dextrose load. She was transferred to a tertiary neonatal unit for the management of acute renal failure. With persistent evidence of only marginally raised liver enzymes and significantly reduced synthetic and excretory function of liver it was unlikely to be explained by solely bacterial or viral illness. Extensive infection screen were negative. Metabolic screening tests were done. She was referred to liver unit. Lip biopsy confirmed the diagnosis of NH. She had a liver transplant on day 36 of life. Histology showed nodular cirrhosis secondary to neonatal haemochromatosis. At age 4 months, she is continuing to thrive well with normal liver function tests. NH is the single most common cause of NLF (40%) and usually presents with severe neonatal liver disease associated with hepatic and extrahepatic iron deposition but sparing the reticulo-endothelial system. NH is hypothesised to be an alloimmune process where maternal antibodies are directed towards fetal liver antigen. Rate of recurrence in subsequent pregnancy is up to 80% and could be effectively prevented by antenatal intravenous immunoglobulin. Early and aggressive medical treatment is essential for improving the outcome. Treatment conundrum of NH continues with some case series showing a success rate of 10 to 20% following a 'cocktail' of antioxidants and chelating agents which have not been evaluated systematically and liver transplantation remains the only definitive treatment.